Discourse strategies that co-construct relational identities in STEM peer tutoring. Issue 3 (3rd July 2019) - Agne, Robert R.; Muller, Heidi L.
ABSTRACT: This study is a discourse analysis of the transcribed talk recorded between tutors and students in a university peer tutoring program. We focus on STEM tutoring sessions, showing how tutors and students co-construct relational identities in and among the technical, highly task-oriented work of solving math and science problems. Using Grounded Practical Theory as a theoretical framework, we propose that understanding the co-creation of relational identities provides insight into an important component of STEM tutoring sessions. Through the process of Action Implicative Discourse Analysis, we describe three conversational practices with which tutors and students negotiate their relational identity—encouragement talk, sensemaking checks, and metadisciplinary talk. We discuss implications in terms of tutoring sessions' situated ideals and participants engaging in a community of practice.